2002
DOI: 10.1079/nrr200244
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting food choice in relation to fruit and vegetable intake: a review

Abstract: The present review provides an investigation into the food choice decisions made by individuals in relation to fruit and vegetable consumption. A comprehensive body of evidence now exists concerning the protective effect of fruit and vegetables against a number of diseases, particularly cardiovascular disease and certain forms of cancer. Current UK recommendations are to increase intakes of fruit and vegetables to 400 g/person per d. In the main body of the review the factors that affect food choice decisions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
238
2
12

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(287 citation statements)
references
References 48 publications
25
238
2
12
Order By: Relevance
“…Hendrickson et al (6) found that fresh F&V at local stores in two urban Minnesota neighbourhoods were not only expensive, but also limited in variety and poorer in quality. These results suggest that the environment in which low-income families obtain food may be one of several barriers to the consumption of a healthy diet, a theme commonly reported in the literature (13)(14)(15)(16) .…”
Section: Discussionsupporting
confidence: 53%
“…Hendrickson et al (6) found that fresh F&V at local stores in two urban Minnesota neighbourhoods were not only expensive, but also limited in variety and poorer in quality. These results suggest that the environment in which low-income families obtain food may be one of several barriers to the consumption of a healthy diet, a theme commonly reported in the literature (13)(14)(15)(16) .…”
Section: Discussionsupporting
confidence: 53%
“…At the individual level, the motivation for food choice may be influenced by factors like sensory appeal, convenience, price, habit, weight control, health concerns and ethical concerns. These factors have also been associated with diet quality in adults, and may explain differences in diet linked to socio-economic status (8,(10)(11)(12)(13)(14)(15) . Individual motives are considered to be modifiable and therefore interesting with regard to health promoting activities.…”
mentioning
confidence: 99%
“…women with low education, low income and/or residing in disadvantaged neighbourhoods) consume diets that are less consistent with guidelines for health, including lower consumption of fruit and vegetables (1)(2)(3) . One explanation for this socio-economic gradient in fruit and vegetable consumption is that women of low SEP are more likely than their more advantaged counterparts to perceive fruit and vegetables as expensive (4)(5)(6)(7)(8)(9)(10) . Women's perceptions of fruit and vegetable affordability, rather than actual prices of fruit and vegetables, have been found to significantly mediate the relationship between SEP and fruit and vegetable consumption (11,12) .…”
mentioning
confidence: 99%